Obesity induced a leptin‐Notch signaling axis in breast cancer. Issue 7 (8th October 2013) - Battle, Monica; Gillespie, Corey; Quarshie, Alexander; Lanier, Viola; Harmon, Tia; Wilson, Kaamilah; Torroella‐Kouri, Marta; Gonzalez‐Perez, Ruben R.
<x xml:space="preserve">Abstract</x> To investigate whether obesity induces a leptin‐Notch signaling axis in breast cancer (BC), leptin‐induced Notch was determined in human MCF‐7 and MDA‐MB231 and mouse E0771 cells and in E0771‐BC hosted by syngeneic lean and diet‐induced obesity (DIO) C57BL/6J female mice. Lean and DIO mice were treated for 3 weeks with leptin inhibitor (PEG‐LPrA2) 1 week after the inoculation of E0771 cells. Leptin induced Notch1, 3 and 4 in BC cells, but Notch2 expression showed opposite pattern in MCF‐7 compared to MDA‐MB231 cells. Notch loss‐of‐function (DAPT and dominant negative [R218H] RBP‐Jk [CSL/CBF1]) showed that a functional leptin‐Notch signaling axis was involved in the proliferation and migration of E0771 cells. E0771‐BC onset was affected by obesity (lean mice7/10 [70%] vs. DIO mice: 11/12 [92%]; Pearson χ2: p = 0.06]). PEG‐LPrA2 significantly reduced BC growth (untreated: 19/42; [45%] vs. treated: 8/42 [19%]; Pearson χ2: p = 0.008). PEG‐LPrA2 did not influence the caloric intake of mice but increased carcass and/or body weights of lean and DIO mice inoculated with E0771 cells, which could be related to the improvement of health conditions (less aggressive disease). Importantly, BC from obese mice had higher levels of Notch3, JAG1 and survivin than lean mice. Inhibition of leptin signaling reduced protein levels of Notch (NICD1, NICD4, Notch3, JAG1 and survivin) and significantly decreased mRNA expression of Notch receptors, ligands and targets. PEG‐LPrA's effects were more prominent in DIO mice. Present data suggest that leptin induces Notch, which could be involved in the reported higher incidence and aggressiveness and, poor prognosis of BC in obese patients.